KONTRIBUSI PERSIAPAN MENGIKUTI KULIAH TERHADAP PRESTASI BELAJAR (STUDI DESKRIPTIF ANALITIK TERHADAP MAHASISWA FKIP UNSYIAH) - Nurhasanah Nurhasanah (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2016)
ABSTRACT : This study aims to determine the contribution of lecturing preparation upon students learning achievement and the most dominant contribution preparation upon student learning achievement. This research uses descriptive quantitative approach. The population in this research were all Guidance and Counselling students of 2007- 2008 generation as many as 120. The research sample was 75% of the population by stratified proportional random sampling technique which amounts to 90 people. Data collection techniques using questionnaires and documentation. Data analysis techniques using simple linear regression and also analyzed the coefficient of determination (r2). The results showed that there is a significant contribution between lecturing preparation and learning achievement at 70.2%. Lecturing preparation which most dominant contribution was non physical preparation at 55.7%, while the physical preparation contribute to 52.7% and lecturing condition at 52%. Conclusion in this study is there is a significant contribution between lecturing preparation and learning achievement. The most dominant contribution preparation is non-physical preparation.Keyword : Preparation Follow College, Learning Achievement - Persiapan Mengikuti Kuliah, Prestasi Belajar.